MANAJEMEN PENGELOLAAN KELAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEDISIPLINAN SISWA - Andi Darman (Institut Agama Islam Negeri Palopo, 2018)
This study aims to find out the Islamic religious education teachers in managing the class and also note it to grade IX students in Malangke Barat 2 Public Middle School North Luwu Regency. This research is a field research that uses a qualitative approach that describes the phenomenon as it is. with data collection techniques, interviews, questionnaires and documentation. The data subjects in this study were PAI teachers of 2 people, students of class IX 71 people.The results of the study are: 1) the efforts of Islamic education teachers in classroom management in improving discipline, showing that: a) Implementing learning methods, conducting room arrangement, and evaluating after the learning process, b) Description of student discipline in each class occurs the noise made by students even though the teacher always reprimanded him and indicated the form of discipline that is the students disturbing each other, students mocked each other when a friend arrived late even though the teacher was in the process of explaining, and students made a fuss when the teacher was permission to leave, c) the correlation between the teacher's efforts Islamic education in the management of teacher classes in classroom management with discipline is closely related to the smooth of learning process. If the teacher is less skilled in classroom management, the learning process is hampered and the teaching objectives are difficult to achieve.